Pesantren dan Pengembangan Studi Islam Berwawasa Gender - Rahmat Fauzi; Ali Marzuki Zebua (Hikmah, 2020)
This article discusses efforts and strategies for developing Islamic studies in Islamic boarding schools that have gender insight. Previous studies on gender and Islamic boarding schools focused more on the socio-cultural dimensions of gender, power relations, women's empowerment, the image of women in the yellow book, figures and agencies. However, there are several studies that have tried to examine efforts to develop gender-based pesantren education at the formal institutional level. Very few have analyzed efforts to develop gender-based Islamic studies in the world of pesantren. This is more due to the difficulty in accepting some pesantren caregivers of the concept of gender equality, which according to them does not come from an Islamic scientific body. Using the integration-interconnection approach developed by Amin Abdullah and Jasser Auda, this paper explains that the development of Islamic studies in pesantren is urgently carried out by utilizing relevant concepts from other sciences such as cultural, social, economic, psychological and so on. Through the so-called scientific interconnections, new Islamic gender insights can be developed and understood more holistically and contextually in the academic environment of the pesantren.